Analysis of information providing for antihypertensive medicines according to the data of Ukrainian web services - O. M. Zaliska; V. S. Huz (Фармацевтичний журнал, 2023)
The digitalization of the pharmaceutical field provides new opportunities to meet patient’s needs and to improve communications, which is important for pharmacies. According to the Law of Ukraine dated 17.09.2020 «On Amendments to Article 19 of the Law of Ukraine "On Medicines" regarding the implementation of electronic retail trade of medicinal products» and Article 81 of the Law of Ukraine «On Medicines» dated 28.07.2022), pharmacies were allowed to carry out electronic retail trade of pharmaceuticals on the condition that information about the right to online trade is entered in the Licensing Register for the manufacture of medicines